The formulation of lubricating grease from waste transformer oil - Nur Suhaila, Anang Japar (2020)
Grease formulation trends were shifting towards greener alternatives. Waste oil generation continues to rise due to industrialization and urbanization. Researches has shown that waste oil can be reused as grease base oil but, the variability of waste oil compositions upon every collection – especially for waste oil generated from automotive industries will contribute to inconsistent grease quality when incorporated in grease formulation. This problem, however, is not apparent for waste oil from the power industry such as waste transformer oil (WTO). In pursuance to overcome the aforementioned problem, this study aims to formulate and produce grease using WTO as a base oil to address the viability of WTO as grease base oil as no grease-WTO-related research had been done. WTO treatment and analysis were predicted significantly associated with the viability of WTO as grease base oil. WTO analysis is carried out to investigate the WTO condition based on its fluid properties, contamination level, and wear metal content. WTO-based sodium and FS greases then formulated, produced, and characterized physically and chemically using standard and non-standard test methods, chosen based on the available equipment. Additive MoS2 is also added into the formulation as to observed how it affect the grease structure and properties. The WTO treatment of settling, filtration, and evaporation are adequate to reduce WTO contaminant concentration to allowable limit and the WTO analysis show that the WTO has good characteristics comparable to most grease base oil and has proved the WTO viability as grease base oil. Grease characterization shows that the WTO content is directly proportional to grease oil bleeding and separation and inversely proportional to the grease consistency and dropping point. Addition of additive MoS2 was found to only slightly affecting the grease properties. WTO-based Sodium and FS grease with desirable properties were successfully formulated and produced using 70% and 92 % WTO content, respectively. The WTO and WTO-based greases however, has poor natural anti-wear properties. On this basis, this study found that WTO can be used as grease base oil and managed to formulate and produce greases using WTO but, further research is needed to improve the grease formulation work and the produced grease quality.